Economic characteristics and produced milk quality in Holstein lactating cows in organic and conventional systems - SHARIFI, M; PAHLAVAN, R; AGHAEI, A; SAFDARI, M (The Indian Journal of Animal Sciences, 2017)
In the past decade, a global demand for products from organic agriculture has increased rapidly. Milk quality is of major interest for all parties. Therefore, the objective of this study was to compare cow performance and product quality in conventional and organic system. Holstein dairy cows (16) were allotted to one of 3 diet groups, including a conventional diet (CON), an organic system with moderate forage (OMF) and an organic system with high forage (OHF). Multiparous cows (3rd and 4th parity) were randomly assigned to the treatments. Range forages were used as part of diets, and cows were offered concentrate and silage two times a day. Daily dry matter intake (DMI) and milk yield were measured across 200 d. Furthermore, somatic cell count, feed cost and feed efficiency were determined at 20-day intervals. MY was different for cows that treated the OHF (22.5 kg/d), OMF (24.9 kg/d), and CON (28.9 kg/d) systems, respectively. Body weights were not affected by treatments; however, differences in body condition scores were observed. Although energy corrected milk and milk urea nitrogen were higher in cows fed CON system; milk fat, phytanic acid, hippuric acid and profit to cost ratio were higher in cows fed organic systems. Additionally, lower feed efficiency, feed cost and blood urea nitrogen were observed in cows fed organic diets.